(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Diabetic nephropathy (DN) is a serious complication of diabetes mellitus involving damage to the capillaries in the glomerulus. This study aimed to explore key genes and signaling pathways participate in the progression of DN. Methods. Two gene expression profile datasets GSE1009 and GSE30528 downloaded from Gene Expression Omnibus (GEO) were used to analyze the differentially expressed genes (DEGs) between DN samples and controls. Coupled two-way clustering (CTWC) and correspondence analysis were performed to explore the potential functions of DEGs. Then, Gene Ontology (GO) terms and pathways associated with DEGs were identified, followed by constructing of the co-expressed gene network and module. Ultimately, the regulatory network based on the DEGs, miRNAs and transcription factors (TFs) was established. Results. Total 283 common DEGs were identified from the two datasets, including 219 down-regulated ones (bone morphogenetic protein 7 (BMP7), decay accelerating factor (CD55) and coagulation Factor V (F5) etc.) and 64 up-regulated ones (inhibin beta c subunit (INHBC) and colony stimulating factor 1 receptor (CSF1R) etc.). The miRNA-TF regulatory network was established with three miRNAs, 8 TFs and 58 DEGs. Besides, three significant pathways including cytokine-cytokine receptor interaction, complement and coagulation cascades and TGF-beta signaling pathways were identified. Conclusion. BMP7, CD55, CSF1R, INHBC and F5 are likely to take crucial roles in the pathogenesis of DN.